Akulturasi Psikologis dan Inovasi Pemuka Agama: Relasi dan Harmonisasi Beragama di Kecamatan Medan Timur - Silva Ardiyanti Ardiyanti; Sepma Pulthinka Nur Hanip (Universitas Islam Negeri (UIN) Mataram, 2022)
Indonesia as a multicultural country supports and respects differences between religions, ethnicities and cultures. Behind this, conflicts between religions have often occurred in recent years, especially in Medan. Therefore, the central role of religious leaders who have understood the psychological community, one of which is by presenting togetherness innovation aims to overcome religious conflict. By using qualitative research with a case study approach that uses the technique of determining the subject of research used by the author is purposive sampling technique that is the process of selecting respondents as subjects based on certain criteria. The results of this study indicate, the role of religious leaders to be central to provide an example to the religious community how to behave and behave in practicing the values of goodness. In addition, innovations such as watching together, respecting traditions, and social assistance to give to each other are important to maintain social harmony.